INFLUENCE OF SMARTPHONES ON STUDENTS` ATTENTIONAL PROCESSES - M. A. Akopova (Вестник университета)
The growing popularity of mobile multimedia technologies determines the need to study the question of what impact they have on our mental sphere. An overview of domestic and foreign publications on the changes in our mental functions under the influence of mobile phones (in particular smartphones) has been given in the article. The results of a study that shows changes in the properties of students’ attention under the influence of intermediate actions with a smartphone also have been presented in the article. The study was carried out in several stages. Using the survey, the features of students ‘ attachment to their gadgets were revealed. According to the results of two experimental series, the features of students ‘ attention properties in the conditions of interaction with smartphones and without them were diagnosed and compared.